No obvious impact of caesarean delivery on childhood allergic outcomes: findings from Australian cohorts. Issue 7 (24th January 2020) - Liao, Zijun; Lamb, Karen E; Burgner, David; Ranganathan, Sarath; Miller, Jessica E; Koplin, Jennifer J; Dharmage, Shyamali C; Lowe, Adrian J; Ponsonby, Anne-Louise; Tang, Mimi L K; Allen, Katrina J; Wake, Melissa; et al.
Abstract : Background and objective: As caesarean delivery and childhood allergy continue to rise, their inter-relationships may change. We examined whether caesarean delivery predicts allergic disease and impaired lung function in two contemporary harmonised population-based cohorts. Methods: Parent-reported asthma and eczema data were drawn from two prospective Australian infant cohorts, HealthNuts (n=5276, born 2006–2010) and the Longitudinal Study of Australian Children (LSAC, n=5107, born 2003–2004) at age 6–7 years, and spirometric lung function from LSAC's Child Health CheckPoint (n=1756) at age 11–12 years. Logistic regression estimated associations between delivery mode and current asthma and eczema at 6–7 years, and linear regression examined lung function at 11–12 years. Models were adjusted for potential confounding factors. Results: Complete case analysis included 3135 HealthNuts and 3654 LSAC children (32.2% and 30.9% born by caesarean, respectively). An association was evident between caesarean delivery and asthma at age 6–7 years in HealthNuts (adjusted OR (aOR) 1.25, 95% CI 1.00 to 1.57) but not in LSAC (aOR 1.05, 95% CI 0.86 to 1.28), while neither study showed clear associations with eczema (HealthNuts: aOR 1.09, 95% CI 0.88 to 1.35; LSAC: aOR 0.89, 95% CI 0.69 to 1.15). Spirometric lung function parameters at age 11–12 years were similar by delivery mode. Associations were not modified by duration of breast feeding, maternal history of asthma/eczema, childcare attendance, number of older siblings or pet exposure. Conclusions: In two unselected populations using harmonised protocols, the likely association of caesarean delivery with developing childhood allergy was small.